Neodymium Oxide-Based Hybrid Phase Few-Layer mos2 Nanocomposite as High-Performance Symmetric Supercapacitor Electrode - Radhalayam, D (Elsevier Ltd, 2024)
The two-dimensional layered materials (for example MoS2) are potential electrodes for supercapacitors with their excellent lamellar structure, high surface area, mechanical flexibility, and potential redox activity. However, due to restacking of chemical structure and low electrical conductivity of the pure MoS2 electrodes are prevented for energy storage applications. Therefore the electrodes are made up of a composite by a mixture of MoS2 and rare-earth metals significantly addressing these issues with improved electrical conductivity, large electrochemical active surface, and shorter ion-diffusion kinetics. In the present study, the MoS2 and MoS2/Nd2O3 composite were synthesized by hydrothermal method. The structural phase identification of prepared samples was accomplished by using an X-ray diffractometer (XRD) and Raman spectra. Furthermore, TEM reveals changes in the shape of nanosheets and interlayer spacing. The GCD of symmetric MoS2/Nd2O3 composite electrodes displayed remarkable charging/discharging performance, with increased stability and rate capability. The MoS2/Nd2O3 composite shows utmost Csp of 2528.18 Fg-1 at 1 Ag-1. In addition, the CV and GCD studies suggest that the electrodes exhibit pseudocapacitive behavior and excellent energy density(E) of 191 Wh kg−1 at 1474.1 W kg−1 power density(P) in 1M H2SO4. The supercapacitor device made up of MoS2/Nd2O3 composite shows greater performance in practical LED glowing applications. Therefore, the composites make advancements in energy storage devices like batteries and supercapbatteries due to their excellent energy storage, high electrochemically active surface area, and stability. © 2024 Elsevier Ltd and Techna Group S.r.l.